A Comparative Study to Evaluate the Educational Impact of E-Learning Tools on Griffith University Pharmacy Students' Level of Understanding Using Bloom's and SOLO Taxonomies. (8th December 2014) - Karaksha, Abdullah; Grant, Gary; Nirthanan, S. Niru; Davey, Andrew K.; Anoopkumar-Dukie, Shailendra
Abstract : Objectives . To design a series of e-learning tools within the framework of a defined educational pedagogy to complement the conventional pharmacology curriculum at Griffith University and evaluate the impact of this strategy on student level of understanding through taxonomic classification of student final exam answers. Methods . A series of 148 e-learning tools was designed for 3rd year undergraduate pharmacy students and incorporated into their curriculum during 2012. The educational benefits of the e-learning tools were evaluated by analyses of student level of understanding (by SOLO taxonomy) at the final exams between the control group (standard curricula) in 2011 and the intervention group (standard curricula + e-learning tools) in 2012. Results . Backward linear regression analysis demonstrated GPA to be the most significant predictor of level of understanding, while the intervention group was a highly significant predictor for greater level of understanding in semester two. Conclusion . E-learning tools appeared to significantly improve student level of understanding as scored by the SOLO taxonomy when students engaged highly with the tools.